PENGARUH PENGAWASAN PIMPINAN TERHADAP PENINGKATAN PRESTASI KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN FAKFAK PROVINSI PAPUA BARAT - MOHAN, SIMSON; Mandey, Jantje; Kiyai, Burhanuddin (Sam Ratulangi University, 2016)
Abstract: This study was conducted based on the results prasurvei that civil servants in performing basictasks and functions indicated yet to reach optimum performance. This is presumably related to theimplementation of policy leadership. Thus, the study aims to